Sustainable Fashion as The Early Awakening of the Clothing Industry Post Corona Pandemic - Kulsum, Umi - (International Journal of Social Science and Business, 2020)
The purpose of writing is an effort to rebuild a more sustainable fashion industry after COVID-19, and to move the fashion industry to adopt a sustainable fashion. The method used was a qualitative method with a qualitative descriptive approach. The technique of collecting data was a literature study or literature study, namely by diligently studying the literature needed in writing. The results of this writing were: (1) The experience of a global pandemic will create awareness of the importance of sustainable fashion, to rebuild the fashion industry after COVID-19 with high-quality durability; (2) Sustainability will be seen as the main product priority by all stakeholders, so by adopting a sustainable fashion concept, fashion industry players are expected to be willing to work together to create innovations that are more environmentally friendly and empower the industry. This paper concludes that the impact of the COVID-19 pandemic has brought together fashion industry players to jointly create sustainable fashion solutions for production, distribution, and consumption, and promote social change, the need for transparency and collaboration towards sustainability.